Divine commitment and human obligation : v. 1 - Freedman, David Noel 1922-; Huddlestun, John R. (Grand Rapids MI Eerdmans, 1997)
Contents : v. 1 : history and religion. Includes bibliographical references.
Keywords: Bible. O.T. -- criticism, interpretation